Partial intestinal obstruction due to childhood refractory Non-Hodgkin's lymphoma, successfully treated with Taxol® - (:unkn) unknown (My University, 2003)
In this report, we present a six-year-old male patient with partial intestinal obstruction due to refractory Non-Hodgkin's lymphoma (NHL) whose partial obstruction was successfully treated with Taxol® without any surgical intervention. Following an unsuccessful treatment attempt to treat his high-grade (stage 3) B-cell lymphoma with standard and second-line chemotherapy regimens he was started on radiotherapy and third line chemotherapy during which he was admitted with partial obstructive ileus as a result of tumor progression. Treatment was continued with Taxol® and resulted in total cure of the ileus with reduction of palpable tumor mass over 24 h without necessitating any surgery. Taxol® (200 mg/m2/week) was administered without any major side effects/toxicities for six courses. A control CT of the abdomen revealed a significant reduction in tumor size. After the next course, the patient developed severe thrombo-cytopenia that unfortunately did not resolve before the patient died as a result of further tumor growth and dissemination. Although there are studies that report response to Taxol® treatment in adult patients with refractory NHL, our review of the literature failed to demonstrate any report about the effectiveness of Taxol® in childhood NHL. In conclusion, our case may indicate that Taxol® can be effective and be administered safely in an outpatient setting in children with refractory NHL with the aim of prolonging the survival without sacrificing good quality of life. Studies on larger number of patients are needed to make a definitive conclusion about the value of Taxol® in refractory childhood NHL.
Keywords: Childhood; Ileus; Non-Hodgkin's lymphoma; Paclitaxel; Primary refractory; Taxol®